2006
DOI: 10.1073/pnas.0601611103
|View full text |Cite
|
Sign up to set email alerts
|

κ-Casein-deficient mice fail to lactate

Abstract: Acquisition of milk production capabilities by an ancestor of mammals is at the root of mammalian evolution. Milk casein micelles are a primary source of amino acids and calcium phosphate to neonates. To understand the role of -casein in lactation, we have created and characterized a null mouse strain (Csnk ؊/؊ ) lacking this gene. The mutant -casein allele did not affect the expression of other milk proteins in Csnk ؊/؊ females. However, these females did not suckle their pups and failed to lactate because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 32 publications
(37 reference statements)
0
33
0
Order By: Relevance
“…In addition, the genetic variation of κ-CN involving the mature protein could be associated with other polymorphisms in the noncoding sequences (promoter, introns), which might be causative mutations for the expression differences between some alleles, as has already been found for the 2 main bovine CSN3 alleles (reviewed by Martin et al, 2002). In all cases, quantitative differences at the κ-CN level must be closely considered because of the essential role of this CN in the process of reproduction in mammals; as recently demonstrated in mice, when a null mutation was introduced in κ-CN, it resulted in destabilization of the CN micelles and lactation failure (Shekar et al, 2006).…”
Section: Association Analysesmentioning
confidence: 99%
“…In addition, the genetic variation of κ-CN involving the mature protein could be associated with other polymorphisms in the noncoding sequences (promoter, introns), which might be causative mutations for the expression differences between some alleles, as has already been found for the 2 main bovine CSN3 alleles (reviewed by Martin et al, 2002). In all cases, quantitative differences at the κ-CN level must be closely considered because of the essential role of this CN in the process of reproduction in mammals; as recently demonstrated in mice, when a null mutation was introduced in κ-CN, it resulted in destabilization of the CN micelles and lactation failure (Shekar et al, 2006).…”
Section: Association Analysesmentioning
confidence: 99%
“…All milks contain an ortholog of κ-CN and, in the 6 examples where the composition of casein has been determined (Supplementary Table S1; http://dx.doi.org/10.3168/jds.2013-6831), the percentage of κ-CN in whole casein varies from less than 2% to more than 17% (Baranyi et al, 1995;Miranda et al, 2004;Boumahrou et al, 2009;Holt and Carver, 2012). So vital is this stabilization for the proper formation and functioning of casein micelles that mice made deficient in κ-CN fail to lactate (Shekar et al, 2006).…”
Section: Safe Secretion Of High Concentrations Of Potentially Fibrillmentioning
confidence: 99%
“…It has also been suggested that the genetic variation in CSN3 implies that the mature protein could be associated with other polymorphisms in the non-coding sequences (promoter), which could be mutations that cause dierent expressions among some alleles, such as two main alleles in the CSN3 gene in bovine cattle (Martin et al 2002). Existing evidence has shown that when a null mutation was introduced in CSN3 and caused the destabilization of the casein micelles, there was a failure in the lactation process (Shekar et al 2006).…”
Section: Resultsmentioning
confidence: 99%